Athletics 365: Building the foundations for the next generation of athletics champions - Grace, S. (New Studies in Athletics, 2014)
Athletics 365 is a teaching and coaching programme created in the United Kingdom by England Athletics as a part of a wider effort to improve how the sport at the grassroots level retains and develops young athletes. The philosophy of the programme emphasises a multi-event approach and the process of acquiring skills ('how' to run, jump or throw) rather than the outcome (time or distance achieved). After a successful 2009 pilot project, the Athletics 365 Curriculum has been rolled out across the country and integrated in the British Athletics Coach Education System. It has already made significant impacts on the operation of athletics clubs, the retention of young athletes and the profile of coaches in the UK and the support materials (coaching cards, videos, athlete handbooks, etc.) have attracted interest from coaches and teachers in a number of other countries. The project was named the Overall i/Vinner for 2014 in the prestigious European Athletics Innovation Awards. In this report, the background, development process and roll-out of the programme are described and five recommendations for the future are given.